Funding the Cooperative City From knowledge network to local action - Patti, Daniela; Polyak, Levente (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
In recent years, cultural, social, community and educational spaces have become laboratories of new forms of living, working, learning and collective exchange. However, these civic spaces face many difficulties in establishing stable economic structures, or lack financial buffers to secure their long-term operations and relative autonomy. This book brings together a variety of actors, practices, models, mechanisms and opinions that address these difficulties: our intention is to use these experiences to help and inspire civic space initiatives in accessing community capital, building stable financial models, strengthening local economies by keeping profits in neighbourhoods and ensuring spaces against public oppression or the extraction economy.